Al-Taḥlīl al-Naqdī li al-Kitāb al-Ṭālib fī Māddah al-Lughah al-‘Arabiyyah li al-Ṣaff al-Ḥādī ‘Ashar wifqa Manhaj 2013 (Wizārat al-Syu’ūn al-Dīniyyah al-Indūnīsiyyah, 2015) - Azzahro, Vivia Salma; Muhaiban, Muhaiban (Civil Officium: Journal of Empirical Studies on Social Science, 2025)
This study aims to conduct an in-depth review of the Buku Siswa Bahasa Arab Kelas XI Madrasah Aliyah (MA) Kurikulum 2013 Edisi 2015, focusing on four main aspects: content, material organization, instructional presentation, and layout design. The book is designed to support the implementation of the 2013 Curriculum, which is oriented towards a scientific approach and the development of students' character. The method used in this research is qualitative descriptive, with content analysis techniques that allow the researcher to identify the strengths and weaknesses from both pedagogical and visual perspectives. The analysis results indicate that although this book adheres to the standard basic competencies set out in the curriculum, several significant weaknesses exist. In terms of content, some material is considered less relevant to the socio-cultural context of Indonesian students. Regarding organization, the sequence and continuity between chapters are not fully logical or progressive. The presentation of the material also tends to be less interactive and one-directional, with limited variation in media or methods of delivery. From a visual and design perspective, the book does not have an optimized reading comfort, such as font selection, the layout of images and texts, and the quality of illustrations. This affects students' reading interest and comprehension. Therefore, updates and more contextual and communicative developments are necessary to make the book more suitable for the characteristics of current MA students and the demands of the competency-based curriculum. This study concludes that, although the book has met some of the basic elements of the curriculum, a comprehensive revision is needed, particularly in strengthening the relevance of the content, the connection between topics, variation in presentation methods, and improvements in visual design. These updates are crucial to ensure that the book serves as a teaching tool and encourages students' active participation, understanding, and engagement in the Arabic learning process in a holistic and meaningful way.